All-fiber optical polarization modulation system using MoS2 as modulator - Ahmad, Harith; Lim, Hwee San; MatJafri, Mohd Zubir; Ge, Yan Qi; Zhang, Han; Tiu, Zian Cheak (Elsevier, 2019)
In this work, an MoS2 thin film is used as a modulator in an all-optic polarization modulation system. Polarization modulation is achieved using the thermo-optic effect to modify the refractive index of the MoS2 thin film, changing the polarization state of the incident signal light. A high intensity laser signal is pumped into the MoS2 thin film to generate heat, and due to the thermo-optic effect the refractive index of the MoS2 thin film is modified, causing the polarization state to be modulated accordingly. The azimuth degree is rotated almost linearly with the increase of the pump power and a 70.81° azimuth shift is achieved within the available pump power range. A polarization modulation of 0.1304°/mW with a hysteresis difference of 3.22% is reported in this work. The proposed system has significant potential for use in optical fiber communication systems, optical frequency domain imaging, pulsed lasers and optical signal encoding. © 2019 Elsevier B.V.